2006
DOI: 10.1103/physreva.74.023402
|View full text |Cite
|
Sign up to set email alerts
|

Photodetachment ofHby a short laser pulse in crossed static electric and magnetic fields

Abstract: We present a detailed quantum mechanical treatment of the photodetachment of H − by a short laser pulse in the presence of crossed static electric and magnetic fields.An exact analytic formula is presented for the final state electron wave function (describing an electron in both static electric and magnetic fields and a short laser pulse of arbitrary intensity). In the limit of a weak laser pulse, final state electron wave packet motion is examined and related to the closed classical electron orbits in crosse… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 77 publications
(176 reference statements)
0
3
0
Order By: Relevance
“…One of the main strengths of the GK theory is that it yields very reliable quantitative results over a wide range of laser intensities and frequencies for both the perturbative and nonperturbative regimes. Increasing interest in the role the CEP plays in the photodetachment of negative atomic ions in few-cycle laser pulses [15][16][17][18][19][20] motivated us recently to adapt the GK formalism to ultrashort linearly polarized pulses [21]. There we showed that application of the saddle-point method to the amplitude for a laser pulse with N optical cycles [e.g., of the form A(t) ∝ sin 2 (ωt/2N ) sin(ωt + α)] produces 2(N + 1) saddle points in complex time.…”
Section: Introductionmentioning
confidence: 99%
“…One of the main strengths of the GK theory is that it yields very reliable quantitative results over a wide range of laser intensities and frequencies for both the perturbative and nonperturbative regimes. Increasing interest in the role the CEP plays in the photodetachment of negative atomic ions in few-cycle laser pulses [15][16][17][18][19][20] motivated us recently to adapt the GK formalism to ultrashort linearly polarized pulses [21]. There we showed that application of the saddle-point method to the amplitude for a laser pulse with N optical cycles [e.g., of the form A(t) ∝ sin 2 (ωt/2N ) sin(ωt + α)] produces 2(N + 1) saddle points in complex time.…”
Section: Introductionmentioning
confidence: 99%
“…Second η 1 ⇔ ω B ω, in this limiting situation the slowly varying electric field can be considered as constant since the time scale is dominated by the synchrotron frequency, i.e. both fields can be considered as static [17,18,32]. Third η ≈ 1 ⇔ ω B ≈ ω, this is perhaps the most interesting case, the time scale of the magnetic field effects is akin to that of the electric field and both effects compete.…”
Section: Photodetachment Rate: Numerical Experimentsmentioning
confidence: 99%
“…The main motivation of this work is to study the effects of the transverse magnetic field in the generation of closed trajectories, and their manifestation in the photodetachment modulation. We consider as references the limiting cases of no magnetic field [23,31], as well as the case of perpendicular static electric and magnetic fields [17,18,32], and we discuss the differences.…”
Section: Introductionmentioning
confidence: 99%